Developing and evaluating utility of school-based intervention programs in promoting leisure-time physical activity: An application of the theory of planned behavior - Chatzisarantis, Nikos; Kamarova, S.; Kawabata, M.; Wang, J.; Hagger, Martin (Edizioni Luigi Pozzi S.r.l., 2015)
Building upon tenets of the theory of planned behavior, the present study examined whether school-based intervention programs that aimed to change attitudes, perceptions of control, or both attitudes and perceptions of control in combination, was successful in promoting participation in leisure time physical activities. Participants were 1372 pupils recruited from 10 secondary schools and exercised for less than 3-days per week in the previous month. Using a cluster-randomized design, participants were presented with one of the intervention conditions each lasting 10 minutes delivered as part of physical education classes twice per week over a period of 8 weeks. The interventions included: (i) an attitude-based intervention that targeted salient behavioral beliefs; (ii) a second attitude-based intervention that targeted non-salient behavioral beliefs; (iii) a control-based intervention program that targeted salient control beliefs; and (iv) a combined intervention program that targeted both salient control beliefs and salient behavioral beliefs. Results indicated that while all of the intervention programs resulted in increased participation in leisure time physical activity, the combined intervention program targeting change in attitudes and perceptions of control was least effective. Overall, the findings suggest that schools and teachers can promote leisure time physical activity through brief cost-effective interventions.